Training Load-Recovery Mismatch and Injury Occurrence in Competitive Athletes: Insights From Longitudinal Monitoring - Ülkü Çoban; Merve Uca; Esma Atalan; Ednan Ayvaz (Sports Health: A Multidisciplinary Approach, 2026)
Background: Training load is widely recognized as an important contributor to injury occurrence in sport; however, athletes exposed to similar workloads may differ in their ability to tolerate and recover from training demands. Hypothesis: Injury occurrence in competitive athletes is hypothesized to be more strongly associated with the interaction between training load and recovery status than with training-load magnitude alone, and reductions in recovery status are expected to precede injury onset. Study Design: Retrospective longitudinal observational study. Level of Evidence: Level 3. Methods: A retrospective longitudinal dataset comprising 15,420 monitored training sessions from 156 competitive athletes was analyzed. Training load was quantified using session-based workload measures derived from training intensity and duration. Recovery status was evaluated using a composite indicator derived from sleep quality, perceived recovery, fatigue, and stress-related measures. Injury outcomes were examined using generalized estimating equation logistic regression models to account for repeated observations within athletes. Results: Higher training loads were associated with greater injury occurrence (odds ratio [OR], 1.15; 95% CI, 1.02-1.30), whereas higher recovery status was associated with lower injury odds (OR, 0.97; 95% CI, 0.97-0.98). The association between training load and injury occurrence was more pronounced among athletes with impaired recovery, while comparable workloads showed weaker associations when recovery status was moderate or high. Recovery levels declined across the sessions preceding injury onset, with the largest reductions observed during the final sessions before injury. Conclusion: Injury occurrence in competitive athletes appears to be more closely associated with the interaction between training load and recovery status than with training-load magnitude alone. Monitoring recovery alongside training load may help practitioners identify periods of increased injury vulnerability and adjust workloads according to changes in athlete recovery status. Clinical Relevance: Evaluating recovery status alongside training load may help practitioners identify short-term periods of increased injury vulnerability and guide context-sensitive adjustments to training demands in competitive athletes.